2019
DOI: 10.3390/w11040868
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vertical Migration and Leaching of Nitrogen in Percolation Water of Paddy Fields under Water-Saving Irrigation and Straw Return Conditions

Abstract: The use of water-saving irrigation techniques has been encouraged in rice fields in response to irrigation water scarcity. Straw return is an important means of straw reuse. However, the environmental impact of this technology, e.g., nitrogen leaching loss, must be further explored. A two-year (2017–2018) experiment was conducted to investigate the vertical migration and leaching of nitrogen in paddy fields under water-saving and straw return conditions. Treatments included traditional flood irrigation (FI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…The NO 3 -N flux in the root environment was greater for some weeks after transplanting, while it decreased subsequently as the vegetative cover of pepper increased. In line with this study, a study in China showed that the NO 3 -N concentrations in percolated water was in a regular decreasing pattern from drier to wetter phases of irrigated straw-mulched rice production [41]. Consistent result of NO 3 -N load in the leachate was also reported by Govaerts et al [42] in the CA experiment conducted in Mexico.…”
Section: Effects Of Ca On the Nitrogen Movementsupporting
confidence: 88%
“…The NO 3 -N flux in the root environment was greater for some weeks after transplanting, while it decreased subsequently as the vegetative cover of pepper increased. In line with this study, a study in China showed that the NO 3 -N concentrations in percolated water was in a regular decreasing pattern from drier to wetter phases of irrigated straw-mulched rice production [41]. Consistent result of NO 3 -N load in the leachate was also reported by Govaerts et al [42] in the CA experiment conducted in Mexico.…”
Section: Effects Of Ca On the Nitrogen Movementsupporting
confidence: 88%
“…Figure A3 shows that the largest share was that of the nitrate form. This relates to its negative charge and to the low affinity of soil adsorption complex to the N min form [37,38]. The measured values point to the significantly highest loss (p < 0.05) of N min in the NPK variant, where MF was applied, when compared to the other variants.…”
Section: Leaching Of Mineral Nitrogenmentioning
confidence: 92%
“…It can also be applied in sites prone to N substance leaching, e.g. to watercourses or groundwater resources [9,38] because CP composition is specific (humic substances, polysaccharides, etc.) as it contains a considerable amount of stable organic substances [11].…”
Section: Leaching Of Mineral Nitrogenmentioning
confidence: 99%
“…The annual average temperature of the area is 15.3 • C, the mean annual precipitation is approximately 1073 mm and the mean annual evaporation is around 900 mm [35]. During the experiment study, the daily meteorological data, including air temperature, wind speed, relative humidity, precipitation, total solar radiation and so on, were collected by an automated weather station in the study site [36]. The main physical properties of the pre-experiment soil are listed in Table 1.…”
Section: Study Site Descriptionmentioning
confidence: 99%